2016
DOI: 10.3389/fimmu.2016.00379
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin Treatment of Mice with Premalignant Oral Lesions Sustains Cytokine Production and Slows Progression to Cancer

Abstract: Current treatment options for head and neck squamous cell carcinoma (HNSCC) patients are often ineffective due to tumor-localized and systemic immunosuppression. Using the 4-NQO mouse model of oral carcinogenesis, this study showed that premalignant oral lesion cells produce higher levels of the immune modulator, PGE2, compared to HNSCC cells. Inhibiting prostaglandin production of premalignant lesion cells with the pan-cyclooxygenase inhibitor indomethacin stimulated their induction of spleen cell cytokine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Whether or not the transiency of the PD-1 antibody-associated increases in cytokine levels in the spleen and tongue in our premalignant oral lesion model is due to shifts to other immune checkpoints or due to interference in IFN-γ signaling has not yet been determined. What we had previously demonstrated was an increase in production of the inhibitory mediator PGE 2 by premalignant lesion cells at time points similar to the last time point assessed in the present study [30]. Furthermore, this latter study had also shown that treatment of lesion-bearing mice with indomethacin to block prostaglandin production increased production of IFN-γ.…”
Section: Discussionsupporting
confidence: 87%
“…Whether or not the transiency of the PD-1 antibody-associated increases in cytokine levels in the spleen and tongue in our premalignant oral lesion model is due to shifts to other immune checkpoints or due to interference in IFN-γ signaling has not yet been determined. What we had previously demonstrated was an increase in production of the inhibitory mediator PGE 2 by premalignant lesion cells at time points similar to the last time point assessed in the present study [30]. Furthermore, this latter study had also shown that treatment of lesion-bearing mice with indomethacin to block prostaglandin production increased production of IFN-γ.…”
Section: Discussionsupporting
confidence: 87%
“…Johnson and Young evaluated the efficacy of indomethacin using the 4-NQO mouse model of oral carcinogenesis. This study indicates that inhibition of prostaglandin production in the precancerous lesion phase increases immune capacity and improves clinical outcomes [99].…”
Section: Immunotherapy: Can the Modulation Of The Immune Response Thrmentioning
confidence: 66%
“…Studies to assess the mechanism by which premalignant oral lesion cells alter cytokine levels systemically demonstrated that the stimulation of Th1 and Th17 cell-associated cytokines was through soluble mediators produced by premalignant lesion cells [ 52 , 55 ]. The induction of some, but not all, of the inflammatory mediators was blocked by inhibiting cyclooxygenase in premalignant lesion cells, suggesting that lesion cell-derived PGE 2 could be contributing to some of the systemic inflammation [ 56 ].…”
Section: Systemic Immune Alterations Associated With Premalignant Lesmentioning
confidence: 99%
“…Studies have also suggested that the increase in CD8 + cells within intraepidermal carcinomas, which are an earlier stage of cancer, might be responsible for their regression following dermal cytokine-inducing treatments [ 35 ]. An indirect form of immunotherapy for mice bearing premalignant oral lesions has aimed to temper the inflammatory state by inhibiting production of prostaglandins, which can function both as inflammatory mediators and as inhibitors of Th1 immune reactivity [ 56 ]. This approach stimulated levels of IFN-γ-expressing CD8 + cells locally within regional lymph nodes and distally in the spleen.…”
Section: Immunological Treatment Approaches For Premalignant Lesionsmentioning
confidence: 99%